Effect of feeding streptococcus faecium to artificially reared pigs - E F Kluber III; D S Pollmann; Frank Blecha (Kansas Agricultural Experiment Station Research Reports, 1983)
Two trials were conducted with a total of 112 artificially reared pigs to evaluate the effect feeding Streptococcus faecium. The areas studied were growth and feed efficiency, mortality rate, daily scour score, blood parameters (total leukocyte numbers and differentials), and in vivo determination of cell-mediated immunity. The results of the trial indicate that there was no significant advantage to feeding Streptococcus faecium to artificially reared pigs.; Swine Day, Manhattan, KS, November 10, 1983
Keywords: Swine day; 1983; Kansas Agricultural Experiment Station contribution; no. 84-174-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 442; Swine; Streptococcus faecium; Artificially reared pigs